The current state of factoring operations in agriculture of Ukraine - Komarova, K. (ТДАТУ, 2019)
This article discusses peculiarities of factoring operations in agriculture of Ukraine. The main prospects and its benefits for agricultural enterprises are analyzed.
Keywords: factoring operations; factoring; agricultural sector